Settling with the Norm? : Norm and Variation in Social Groups and Their Material Manifestations in (Roman) Iron Age (800 BC-AD 300) Settlement Sites of the Northern Netherlands - De Vries, Karen M. (Sidestone Press, 2021)
When studying later prehistoric societies, it is evident that shared practices, as well as variations, exist in the settlement record. Traditionally, the emphasis has mainly been on the elements shared on large scales, the widely shared norms. Variations in material culture have received little attention. This is regrettable, because through the study of both norm and variation in material culture, it is possible to understand how people are part of larger com.